FINANCIAL ECOSYSTEM OF THE ENTERPRISE: INTERACTION OF BANKING, INSURANCE MANAGEMENT AND TAX PLANNING - Hranovska, Inna; Makarchuk, Inna; Kryvenko, Yuliia (Current Problems of Sustainable Development, 2026)
The growth of financial risks, increasing tax burden, and instability of the economic environment necessitate the development of effective mechanisms for managing financial resources of domestic enterprises. Under such conditions, the integration of banking, insurance, and tax instruments within a unified system capable of ensuring financial stability and adaptability of business entities becomes particularly important. The purpose of the study is to reveal the essence of the enterprise financial ecosystem and to substantiate  the interaction of banking, insurance management, and tax planning based on analytical data. The research results indicate a strengthening of the role of the banking sector in ensuring enterprise liquidity, as evidenced by the growth of lending volumes and improvement in the quality of loan portfolios. A significant expansion of the insurance market has been identified, reflecting the increased use of risk management instruments and enhanced stability of financial flows. The growth of tax revenues generated by businesses indicates an increased fiscal burden, which directly affects the volume of available financial resources. A model of the enterprise financial ecosystem has been proposed, reflecting the interconnection between banking, insurance, and tax management and enabling the assessment of the level of integration of financial instruments depending on the scale of enterprise activity. The model testing on conditional examples of small, medium, and large businesses demonstrates that a higher level of integration of financial instruments contributes to risk reduction, increased liquidity, and strengthening of financial stability, while also creating opportunities for optimizing financial decisions, aligning credit, insurance, and tax policies, and improving the efficiency of financial flow management in an unstable environment. The scientific novelty lies in the development of an integrated model of the enterprise financial ecosystem that reflects the interdependence of banking, insurance, and tax management and allows assessing the level of integration of financial instruments depending on the scale of business activity.
Keywords: liquidity; financial resources; insurance instruments; tax burden; lending; risk management